The Influence of Profitability, Ownership Structure, Capital Structure, and Firm Size on Dividend Policy in The Health Sector - Ita Florentina Simbolon; Robinhot Gultom; Saur Melianna (Pusat Riset dan Inovasi Nasional, 2025)
The objective of this study is to ascertain and examine the impact of the following factors on dividend policy in health sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period: profitability ratio, ownership structure, capital structure, and company size. The study employed the following variables: the dependent variable (Y), which is Dividend Policy proxied by Dividend Payout Ratio (DPR); the independent variable (X) is the Profitability Ratio proxied by Return on Assets (ROA); the ownership structure proxied by Institutional Ownership (KI); the capital structure proxied by Debt to Equity Ratio (DER); and the company size proxied by Ln (TA). Purposive sampling was used to gather the sample for this investigation. Ten businesses were chosen as research samples based on the criteria and data processing procedure outlined. The study's findings show that the profitability ratio, ownership structure, capital structure, and company size all have an impact on dividend policy at the same time. Dividend policy is influenced by the profitability ratio to some extent. In part, the dividend policy of health sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period is unaffected by ownership structure, capital structure, and company size.